Pedagogical and Intercultural Facets in an International Students’ Research Training Program in Times of Pandemic: A Case Study on “The Intersections' of Gender, Family, and Society in Kyrgyzstan” - Schrader, Heiko; Gorborukova, Galina; Mamatova, Makhinur (International Dialogues on Education Journal, 2022)
This paper discusses the conception of a joint intercultural students’ research program of one German and two Kyrgyzstani teachers and students from the Otto-von-Guericke University of Magdeburg (Germany) and the American University of Central Asia, Bishkek (Kyrgyzstan). The paper conceptualizes such a research training program and gives reference to qualitative methods teaching in the two corresponding universities. What follows is a description of the chosen research topic: “The 'Intersections' of Gender, Family, and Society in Kyrgyzstan”, and the course program. With different academic cultures concerning research ethics in the Anglo-Saxon and continental European contexts, a challenge for such a program will be addressed. A short review of the research results of the different students’ teams is provided, and the paper is finalized with a self-reflection upon such a joint intercultural undertaking.